Economic impact of 2015 transboundary haze on Singapore - Quah, Euston (2022)
We quantify and estimate the economic impact of the transboundary haze pollution in 2015 on Singapore following reliable quantitative methods and techniques in cost-benefit analysis. We include in the estimation both tangible and intangible costs associated to haze pollution. Specifically, in the estimation of the tangible costs of haze, the estimation includes (1) adverse impacts of haze on health, (2) loss in tourism, (3) loss in business as an indirect effect from loss of tourist receipts, (4) productivity loss due to restricted activity days and (5) cost of mitigation and adaptation by government agencies and households. For the estimation of the intangible costs, the value is derived from the contingent valuation study of Quah, Chia, and Tsiat-Siong (2018) which was conducted in 2018 to estimate Singapore residents’ willingness to pay for a pro-environment collaboration project that could effectively stop “slash and burn” practices and significantly reduce the annual haze pollution issue. The total cost of the 2015 haze episode on Singapore which lasted for 2 months is estimated at S$1.83 billion, amounting to 0.45 % of the country's gross domestic product. Accordingly, the total tangible cost is estimated at S$1.46 billion equivalent to 0.36 % of GDP while the total intangible cost stands at S$0.36 billion equivalent to 0.09 % of GDP. The findings have important implications for public policy.